Mesoporous Silica and Titania-Based Materials for Stability Enhancement of Polyphenols - Mioara Prundeanu (MDPI AG, 2021)
To improve phytochemical stability, polyphenolic extracts prepared from Salvia officinalis L., which is a valuable source of phytocompounds with health benefits, were embedded into mesopores of silica, titania, or titania-ceria materials. Ethanolic and hydroalcoholic extracts were prepared by conventional, microwave- or ultrasound-assisted extraction. The influence of the extraction conditions on chemical profile, radical scavenger activity (RSA), and antimicrobial potential of the extracts was assessed. The extracts were characterized by spectrophotometric determination of total polyphenols, flavonoids, chlorophyll pigment contents, as well as RSA. A reverse phase HPLC- PDA analysis was performed for the identification and quantification of extract polyphenols. The extract-loaded materials exhibited an enhanced RSA compared to the free extract after several months of storage, resulting in better polyphenol stability over time following embedding into a mesoporous matrix. Selected extracts free and embedded into mesoporous support were tested against Pseudomonas aeruginosa ATCC 27853, Escherichia coli ATCC 25922, and Staphylococcus aureus ATCC 25923; the best antimicrobial activity was obtained for S. aureus. A slight improvement in antimicrobial activity was observed for the ethanolic extract prepared by ultrasound-assisted extraction following embedding into the TiO2 matrix compared to MCM-41 silica due to the support contribution.